2019
DOI: 10.17645/mac.v7i1.1624
|View full text |Cite
|
Sign up to set email alerts
|

ICT Use and Digital Inclusion among Roma/Gitano Adolescents

Abstract: This article analyses the way in which the digital divide affects Roma/Gitano minors. This ethnic group is a paradigmatic case among socially underprivileged groups in Spain; excluded from industrial society, they appear to be facing a similar situation in the post-industrial era. We, therefore, sought to explore the digital experiences of minors from this group in order to study social and digital exclusion/inclusion among them. The research strategy took a comprehensive approach, covering both offline and on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…Gypsy, Roma, Traveller communities experience significant health inequities linked to higher mortality, morbidity and infant mortality as well as difficulties accessing healthcare (Heaslip et al., 2019). 29 In terms of Gypsy, Roma, Travellers digital access there is a mixed picture in terms of access and connectivity with some writers arguing poor (Garmendia and Karrera 2019) 30 and others noting good access (Salemink 2016) 31 depending upon location in terms of site provision and country of residence. Research in the UK by Scadding and Sweeney (2018) 32 with Gypsies and Travellers identified that 20% had never used the internet, 52% reported low confidence in using the internet and only 38% had a household internet connection and this is much lower than people living outside of these communities.…”
Section: Digital Exclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gypsy, Roma, Traveller communities experience significant health inequities linked to higher mortality, morbidity and infant mortality as well as difficulties accessing healthcare (Heaslip et al., 2019). 29 In terms of Gypsy, Roma, Travellers digital access there is a mixed picture in terms of access and connectivity with some writers arguing poor (Garmendia and Karrera 2019) 30 and others noting good access (Salemink 2016) 31 depending upon location in terms of site provision and country of residence. Research in the UK by Scadding and Sweeney (2018) 32 with Gypsies and Travellers identified that 20% had never used the internet, 52% reported low confidence in using the internet and only 38% had a household internet connection and this is much lower than people living outside of these communities.…”
Section: Digital Exclusionmentioning
confidence: 99%
“…Where Gypsy, Roma, Travellers have a smart phone they typically use this to communicate with other people in the community or family through closed social media sites such as WhatsApp or Facebook (Garmendia and Karrera 2019, Salemink 2016). 30 , 31 Digital literacy is also lower in these communities (Salemink 2016; Garmendia and Karrera 2019), 31 , 30 largely due to poor literacy skills in general (Scadding and Sweeney 2018) 32 and this can inhibit wider use of digitalisation, especially for older people. Salemink2 (2016) 31 argues there is also a gender aspect here as women tended to spend more time at home providing more opportunity to develop digital skills compared to men who they argue are at greater risk of digital exclusion.…”
Section: Digital Exclusionmentioning
confidence: 99%
“…The action research started by identifying the problem that needs intervention and change. Although Roma youths are familiar with online media and use them intensively in their daily lives (Garmendia & Karrera, 2019), they often present an inability to critically analyse the causes of online hate speech and manage it effectively. Thus, they end up being or feeling inactive, resigned, marginalized, impulsive and/or aggressive.…”
Section: Research Identitymentioning
confidence: 99%
“…With adequate digital literacy, e-inclusion will be achieved, as the assumption, application, and promotion of accessibility standards and guidelines through training and education [35][36][37][38]. Its purpose is to ensure that no one is left behind in using the benefits of ICT and focuses on the participation of all people and communities in all aspects of the Information and Knowledge Society, with the fundamental objective of reducing gaps in the use of ICTs and to promote their use to overcome e-exclusion and improve economic performance, employment opportunities, quality of life, participation, and social cohesion [39].…”
Section: E-exclusionmentioning
confidence: 99%